Fringe more than context: Perceived quality of life in informal settlements in a developing country: The case of Kabul, Afghanistan. (December 2020) - Shahraki, Saeed Zanganeh; Hosseini, Ali; Sauri, David; Hussaini, Fatema
Highlights: Informal settlements occupy more than two-third of the residential area and represent about four-fifth of the city population. In Kabul, both formal and informal settlements are mixed. Therefore, some municipal services and facilities for formal residences can be also used by informal settlements. This study showed overall satisfaction with the quality of life indicators in Kabul informal settlements was low, that it causes instability in different indicators of this city. Abstract: Investigations of the quality and satisfaction of urban life in informal settlements remain largely overlooked in the existing literature especially in developing countries. About one-fifth of Afghanistan population is living in urban areas, however, the trend is changing very fast and the country observes now one of the highest urbanization rates in the world. Two principal reasons for rapid urbanization are the return of Afghan immigrants from other countries after a period of relative peace and domestic rural-urban migration. Kabul, the capital city, is the most attractive destination for all immigrants. Around 80 percent of the population of the city lives in informal and illegal settlements. To investigate the perceived quality of life (QoL) of citizens living in these settlements, a survey was administered to 400 households in informal areas of Kabul. Statistical treatment of the results, including regression and factor analysis, showed a general dissatisfaction with the quality of life components related to transportation, leisure, and governance. Material deprivation regarding basic services (water, energy, etc.) was also widespread. On the other hand, less tangible components such as sense of community and family scored higher. Still, informal settlements constitute a fundamental part of Kabul and authorities should seek to improve quality of life especially in what concerns the provision of urban public goods. The findings of this study attempt to provide basic results for managers, planners and urban policymakers to facilitate a reasonable evaluation of the current state of the city in order to take action in addressing planning problems and achieving urban sustainability.